2021
DOI: 10.1093/heapol/czaa188
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to knowledge translation activities within academic institutions in low- and middle-income countries

Abstract: The barriers and facilitators of conducting knowledge translation (KT) activities are well-established but less is known about the institutional forces that drive these barriers, particularly in low resource settings. Understanding organizational readiness has been used to assess and address such barriers but the employment of readiness assessments has largely been done in high-income countries. We conducted a qualitative study to describe the institutional needs and barriers in KT specific to academic institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…We conducted a qualitative study with participants in academic institutions in six countries (Bangladesh, Democratic Republic of the Congo (DRC), Ethiopia, India, Indonesia and Nigeria) to identify barriers and determinants of institutional capacity to conduct KT activities across diverse LMICs contexts, and found that soft-skills (ie, communication, self-awareness and adaptability), robust networks, and alignment between institutional priorities and incentives are important factors that shape institutional capacity to conduct KT activities in LMICs. 9 While strategies such as trainings, mentorship and institutional leadership engagement have been developed to address these barriers and determinants, 10 11 these strategies have been mostly applied to academic institutions in high-income countries (HICs), [12][13][14] with limited empirical evidence of their effectiveness in LMIC settings. 15 Irrespective of the strategies enacted to address barriers to conducting KT activities, academic institutions need to be self-aware of their role in KT and their readiness to undertake relevant KT activities addressing priority health issues to be successful.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a qualitative study with participants in academic institutions in six countries (Bangladesh, Democratic Republic of the Congo (DRC), Ethiopia, India, Indonesia and Nigeria) to identify barriers and determinants of institutional capacity to conduct KT activities across diverse LMICs contexts, and found that soft-skills (ie, communication, self-awareness and adaptability), robust networks, and alignment between institutional priorities and incentives are important factors that shape institutional capacity to conduct KT activities in LMICs. 9 While strategies such as trainings, mentorship and institutional leadership engagement have been developed to address these barriers and determinants, 10 11 these strategies have been mostly applied to academic institutions in high-income countries (HICs), [12][13][14] with limited empirical evidence of their effectiveness in LMIC settings. 15 Irrespective of the strategies enacted to address barriers to conducting KT activities, academic institutions need to be self-aware of their role in KT and their readiness to undertake relevant KT activities addressing priority health issues to be successful.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The results from the consultation process are described in more detail elsewhere. 9 The constructs identified from the literature review and the cross-cutting themes from the consultation process were organised into a quantitative tool with 5 domains and 76 items, with new items developed for the themes. A total of nine additional questions on demographics, facilitators, and barriers to doing KT were added to translate the tool into a survey questionnaire (online supplemental appendix 1).…”
Section: Stakeholder Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Translating research evidence into policy and practice, or knowledge translation (KT), entails a "dynamic and iterative process that includes synthesis, dissemination, exchange and ethically sound application of knowledge to improve health, provide more effective health services and products and strengthen the healthcare system" (9). Limited institutional support and/or buy-in from leadership and relevant stakeholders for KT has been linked to several challenges (10,11,12,13,14), for example: poor infrastructure and inadequate nancial and technical resources speci cally for KT, inadequate soft skills, relationships and networks amongst evidence producers and evidence users negative attitudes and poor knowledge about what KT is and how to do it, and scarce local research evidence relevant to micro-level policy and practice, amongst others (10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%